Conflicts of interest and handling mechanisms in public finances management - Pascal Wilmar Yehezkiel Toloh (Komisi Pemberantasan Korupsi, 2024)
The practice of mitigating conflicts of interest remains vulnerable in the management of public finances. This vulnerability is attributed to issues related to the integrity of state officials, the lack of comprehensive regulations, and the unstructured and systematic aspects of enforcing ethical standards and conflict of interest practices. The objective of this research is to conceptualize effective anti-conflict of interest regulation within Indonesia's legal system and to formulate strategies for addressing conflicts of interest practices in the management of public finances through institutional approaches and financial accountability systems. This research uses normative legal methods. The results indicate the following: first, regulations in Indonesia have not yet been able to accommodate efforts to prevent and enforce action against conflict of interest practices in the conduct of state affairs, especially in the management of public finances, due to overlapping rules and unclear sanction regulations; second, the enforcement of ethical standards concerning conflict of interest practices can be achieved through the establishment of a national ethics commission; third, there is a need to strengthen the audit system and implement internal improvements within the State Audit Agency (BPK). Externally, institutional consolidation in the sectors of financial examination and public financial accountability is required. This can be achieved through the creation of an integrated national financial examination center, serving as the coordinating hub for financial examinations and prevention of financial losses to the state. This would contribute to the development of strategic policies for the management of public finances, with the goal of being free from corrupt practices.